Eugenia veraguensis (Myrtaceae), a new species from Golfo de Chiriquí in Veraguas Province, Panama, with notes on Eugenia rhombea - Flores, Rodolfo; Ibáñez, Alicia; Correa, Mireya D. A. (Phytotaxa, 2016)
Eugenia veraguensis is described as a new species of Myrtaceae from Panama. It differs from E. rhombea, the most similar taxon, by a combination of its shrubby habit, a distinctive dichotomous branching pattern with 4 to 6 leaved branchlets, chartaceous or subcoriaceous leaves and its small number of stamens. It occurs in coastal forest and scrub on islands off Pacific Western Panama. Following the inclusion of a specimen of E. veraguensis as E. rhombea in Flora Mesoamericana, we discuss the occurrence of this latter species in Panama.